Cyber Patrol Strategy in Preventing Online Gambling by the Sukabumi District Police - Juliansyah, Bima Cahya; Setyabudi, Chairul Muriman; Suryadi, Suryadi (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to analyze the effectiveness of cyber patrol strategies implemented by the Sukabumi District Police (Polres Sukabumi Kabupaten) in preventing online gambling, a type of cybercrime that continues to grow in line with the increasing use of digital platforms in society. A qualitative approach with case study methodology is applied to explore in depth the planning, organization, implementation, and control of cyber patrols, as well as the coordination between internal police units and external stakeholders such as Kominfo, ISPs, and financial institutions. Research findings indicate that although regulatory frameworks and operational procedures are available, challenges remain, including limited digital forensic capacity, budget constraints, and low public participation in reporting gambling-related activities. SWOT analysis and the application of Situational Crime Prevention (SCP) theory reveal the need for capacity building of personnel, adoption of advanced detection technologies, and expansion of public education campaigns to strengthen community involvement in online crime prevention. This study recommends the formulation of integrated policies that combine cyber patrol operations with digital literacy, law enforcement, and cross-sector collaboration to create a safer digital ecosystem and reduce the prevalence of online gambling in the Sukabumi District jurisdiction.